Cell adhesion on different titanium-coated surfaces - Resende,Cristiane X. (2010)
Titanium (Ti) is a biocompatible material, and calcium phosphate coating on titanium is commonly applied in order to obtain faster osseointegration around metallic implant. Osteoblast adhesion on three different Ti surfaces was evaluated. The investigated surfaces were commercially pure Ti (cp Ti), Ti coated with sodium titanate (Na-Ti), and Na-Ti followed by octacalcium phosphate coating (Ti-OCP) done by immersion in a calcium and phosphate-rich solution. The studied materials exhibited different morphology and composition. However, all the surfaces promoted cellular adhesion and showed cytocompatibility. No statistically significant difference was observed among the evaluated samples in relation to the number of cells.